The Tazkiyatun Nafs Approach to Overcoming Social Media Addiction in Teenagers - Arham, Abd. Basith; Kulsum, Ummi (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
Social media has become an alternative way to interact without exerting energy, especially among teenagers, using only a mobile phone and the internet. The massive popularity of social media has led to negative impacts, such as anxiety, depression, and decreased productivity, requiring interventions that focus not only on behavior but also on the spiritual dimension. The tazkiyatun nafs (self-control) approach in Islamic counseling is expected to provide a solution to address the phenomenon of social media addiction among adolescents. The primary focus is on applying the core concepts of tazkiyatun nafs, namely muhasabah (introspection), taubat (regret and commitment), and qana’ah (sufficiency), as a healing strategy. This study used a library research approach in conjunction with a descriptive qualitative method. Data collection was conducted through fieldwork from journal reviews, books, research reports, and other sources. The analysis indicates that muhasabah plays a role as the first step in raising adolescents’ awareness of the source of their addiction. Furthermore, the process of taubat (repentance) supports the determination to make changes, while instilling the value of qana’ah (contentment) can act as spiritual protection that reduces social media addiction.